2021
DOI: 10.1002/1348-9585.12263
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ice slurry and carbohydrate–electrolyte solutions for firefighters

Abstract: Objectives To examine the thermoregulatory and fluid‐electrolyte responses of firefighters ingesting ice slurry and carbohydrate–electrolyte solutions before and after firefighting operations. Methods Twelve volunteer firefighters put on fireproof clothing and ingested 5 g/kg of beverage in an anteroom at 25°C and 50% relative humidity (RH; pre‐ingestion), and then performed 30 minutes of exercise on a cycle ergometer (at 125 W for 10 minutes and then 75 W for 20 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…An operational issue of ice slurry intake was the high intake amount required to obtain a significant effect, as described above. Recently, however, it was suggested that even intake of a small amount of ice slurry prepared using a carbohydrate-electrolyte solution as the carrier may provide a cooling effect [ 29 ]. Therefore, in the present study, the participants were asked to ingest a smaller amount of low-temperature ice slurry than that examined in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An operational issue of ice slurry intake was the high intake amount required to obtain a significant effect, as described above. Recently, however, it was suggested that even intake of a small amount of ice slurry prepared using a carbohydrate-electrolyte solution as the carrier may provide a cooling effect [ 29 ]. Therefore, in the present study, the participants were asked to ingest a smaller amount of low-temperature ice slurry than that examined in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we considered that lowering the temperature of the ingested ice slurry might be a more effective cooling strategy than increasing the amount of intake. Tabuchi et al [ 29 ] reported that the use of carbohydrates and electrolytes as solvents may reduce the freezing point of ice slurry and aid in keeping the temperature of the ice slurry below −1°C. Moreover, intake of 5 g·kg -1 of low-temperature ice slurry (−1.7°C) prepared using a carbohydrate-electrolyte solution, which is lower than the intake amount prescribed in previous studies, before exercises attenuated the increase in the core temperature in firefighters [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal cooling involves the introduction of a cold medium to the body through the mouth (and/or nose, in the case of breathing), and includes the consumption of cold fluids or ice and inhalation of cold air [ 6 ]. In recent years, ingestion of ice slurry before working has attracted attention as a practical precooling method and has been reported to suppress the elevation of body temperature [ 2 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clarifying how the contents of ice slurries can be optimized for physiological responses or exercise performance is of critical importance. In a previous study, an ice slurry with a temperature of −1°C was made using a commercially available sports drink containing electrolytes in addition to approximately 4–8% carbohydrates [ 10 , 11 ]. The use of a high-carbohydrate ice slurry (HCIS) containing electrolytes may enable an internal cooling technique.…”
Section: Introductionmentioning
confidence: 99%